Alternative Prey and Predator Interference Mediate Thrips Consumption by Generalists - Smith, Olivia M.; Chapman, Eric G.; Crossley, Michael S.; Crowder, David W.; Fu, Zhen; Harwood, James D.; Jensen, Andrew S.; Krey, Karol L.; Lynch, Christine A.; Snyder, Gretchen B.; Snyder, William E. (Frontiers in Ecology and Evolution, 2022)
Generalist predators’ complex feeding relationships make it difficult to predict their contribution to pest suppression. Alternative prey can either distract predators from attacking pests, weakening biocontrol, or provide food that support larger predator communities to enhance it. Similarly, predator species might both feed upon and complement one another by occupying different niches. Here, we use molecular gut-content analysis to examine predation of western flower thrips (Frankliniella occidentalis) by two generalist predatory bugs, Geocoris sp. and Nabis sp. We collected predators from conventional and organic potato fields that differed in arthropod abundance and composition, so that we could draw correlations between abundance and biodiversity of predators and prey, and thrips predation. We found that alternative prey influenced the probability of detecting Geocoris predation of thrips through a complex interaction. In conventionally-managed potato fields, thrips DNA was more likely to be detected in Geocoris as total abundance of all arthropods in the community increased. But the opposite pattern was found in organic fields, where the probability of detecting thrips predation by Geocoris decreased with increasing total arthropod abundance. Perhaps, increasing abundance (from a relatively low baseline) of alternative prey triggered greater foraging activity in conventional fields, but drew attacks away from thrips in organic fields where prey were consistently relatively bountiful. The probability of detecting Geocoris predation of thrips generally increased with increasing thrips density, but this correlation was steeper in organic than conventional fields. For both Geocoris and Nabis, greater Nabis abundance correlated with reduced probability of detecting thrips DNA; for Nabis this was the only important variable. Nabis is a common intraguild predator of the smaller Geocoris, and is highly cannibalistic, suggesting that predator-predator interference increased with more Nabis present. Complex patterns of thrips predation seemed to result from a dynamic interaction with alternative prey abundance, alongside consistently negative interactions among predators. This provides further evidence that alternative prey and predator interference must be studied in concert to accurately predict the contributions of generalists to biocontrol.